Development Of The PISA-Like Mathematics Literacy Test Based On Yogyakarta Socio-Culture - Sellanidia Antika Sari; Rizqona Maharani; Salvador V. Briones II (Universitas Veteran Bangun Nusantara, 2024)
This research aims to develop a PISA-Like mathematical literacy test based on Yogyakarta socio-culture that is valid, practical and effective. The research method used is Research and Development (R&D) with the Plomp development model. The subjects of this study were 18 students of class VIII of SMP Teladan Yogyakarta. The instruments used included validation sheets, teacher response questionnaires, student response questionnaires, and test instruments. The results of the study showed: (1) the expert validation results obtained a V-Aiken value of 0.75 with a fairly valid category, (2) There were 7 valid and reliable questions, (3) The teacher's response was very good with a score of 50.67, (4) Student responses to test questions obtained 78% of students obtained a score of 38.1 with a good to excellent category, and (5) 72% of students obtained a mathematical literacy test score with a sufficient to good category. Based on the overall data analysis, it can be concluded that the development of a mathematical literacy test instrument based on PISA-Like with the socio-cultural context of Yogyakarta is declared valid, practical, and effective for measuring the mathematical literacy of class VIII students of SMP Teladan Yogyakarta at the prediction level 3.